Sains Kaffah: Aplikasi Konsep Fluida pada Aspek Kaffah - Syahrial Ayub; Wahyudi Wahyudi (Lembaga Bale Literasi, 2025)
This research aims to provide an example of the application of the fluid concept to the Kaffah aspect. Kaffah aspects in clude religion, process, concept, application and meaning. The application of the fluid concept to the Kaffah concept was obtained from literature studies by searching, studying and analyzing and finding a connection between the fluid concept found and the Kaffah aspect. The method in this research is literature review. The research results exemplify the concepts of floating-sink fluids, pressure, aircraft lifting force, density, Bernoulli's principle, Archimedes' law, continuity equation, viscosity and Pascal's law applied to aspects of Kaffah. Science learning is not just about developing science, but also instilling, growing and developing character in students. They are expected to be able to recognize the creator or determiner of nature and all the phenomena that occur to it through the natural laws and scientific theories studied. By getting to know ALLAH SWT through scientific studies, it is hoped that students will be amazed or in awe of Him. This feeling makes them believe and obey Him so that it influences their character in everyday life.